Preparation and characterization of Cu and Ni on alumina supports and their use in the synthesis of low-temperature metal-phthalocyanine using a parallel-plate reactor - Sánchez de la Torre, Fernando; De la Rosa, Javier; Kharisov, Boris I.; Lucio Ortiz, Carlos J. (2013)
Ni- and Cu/alumina powders were prepared and characterized by X-ray diffraction (XRD), scanning electronic microscope (SEM), and N2 physisorption isotherms were also determined. The Ni/Al2O3 sample reveled agglomerated (1 μm) of nanoparticles of Ni (30–80 nm) however, NiO particles were also identified, probably for the low temperature during the H2 reduction treatment (350 °C), the Cu/Al2O3 sample presented agglomerates (1–1.5 μm) of nanoparticles (70–150 nm), but only of pure copper. Both surface morphologies were different, but resulted in mesoporous material, with a higher specificity for the Ni sample. The surfaces were used in a new proposal for producing copper and nickel phthalocyanines using a parallel-plate reactor. Phthalonitrile was used and metallic particles were deposited on alumina in ethanol solution with CH3ONa at low temperatures; ≤60 °C. The mass-transfer was evaluated in reaction testing with a recent three-resistance model. The kinetics were studied with a Langmuir-Hinshelwood model. The activation energy and Thiele modulus revealed a slow surface reaction. The nickel sample was the most active, influenced by the NiO morphology and phthalonitrile adsorption.